Effects of conventional pesticides on the preimaginal developmental stages and on adults of Trichogramma cordubensis (Hymenoptera: Trichogrammatidae). - Vieira, António (2001)
The effects of seven pesticides sprayed on hosts with parasitoids at different phases of egg to adult development (24, 24± 48, 48± 72, 72± 96, 120± 144, 192± 216 h) of Trichogramma cordubensis (Vargas & Cabello) were studied. The effect of these pesticides on the mortality of adult parasitoids upon contact with the hosts immediately or 24 h after the treatments was also tested. One organophosphate insecticide (trichlorfon), one organochlorine insecticide (endosulfan), two pyrethroids (deltamethrin and lambda-cyhalothrin), a commercial formulation of Bacillus thuringiensis subsp. Kurstaki, and two fungicides (acetamide + dithiocarbamete and basic copper sulphate) were selected for testing. All the tests were carried out with fresh solutions of commercial insecticides applied on host eggs at the recommended concentration. The pesticides applied at different development phases did not affect the duration of parasitoid development, except endosulfan, which delayed the parasitoid preimaginal development for one day. With few exceptions, the number of parasitized host eggs that turned black (i.e. with parasitoid prepupae) did not differ significantly between the pesticide treatments and the control. The chemical insecticides affected the adult emergence rates significantly, while the other products resulted in emergence rates similar to control values. The longevity of adult progeny was very short when endosulfan or trichlorfon (< 1 and < 2 days, respectively) were applied. Overall, endosulfan was the pesticide most harmful to the preimaginal development stages of T. cordubensis. Therefore, the use of this product should be avoided when this species is part of an integrated pest control programme.